Drawing inspiration from the spine, designing a pedestrian bridge [spine-inspired design of a pedestrian bridge] - Golkar, Nikoo; Sadeghpour, Amirhossein; Divandari, Javad (Journal of Architecture and Urbanism, 2021)
Natural structures are known to be the source of inspiration for numerous architectural and structural rules in the fields of aesthetics, function, and structure; therefore, the application of the principals governing them could be used for appropriate and optimal design. The present paper was conducted to model the natural structure of load transfer in order to design the structure of a pedestrian bridge with a span of 100 meters. This bridge is located in a mountain park in the tourist area of Kashan, 230 km south of Tehran. For this purpose, by examining the patterns in the nature, which provides a relevant answer to the problem, the spine of animals was identified as the bearing skeleton of the body, the best option for patterning. Inspired by it, a stable structure was designed as a skeleton of a bridge without a middle pillar. Based on a form inspired by the spine of a four-legged animal, the bridge structure was designed. To control the stability of the bridge structure against the loads, the initial design idea was analysed employing the Karamba plugin in Grasshopper software to identify its weaknesses and the final design was obtained. The final design was analysed with SAP2000 structural finite element software to ensure the stability and control of permissible deformations. Additionally, attention to the modular structure of the spine was the source of inspiration for the design of prefabricated elements of the bridge parts, which in addition to reducing the cost of execution, increases the speed of construction of the project. The final design of the pedestrian bridge, which acts similar to a suspension bridge in terms of load transfer and was inspired by the structure of a four-legged vertebrate, is a combination of truss and tensegrity structure and in addition to visual aesthetic, has optimal structural performance.